Oldest record of Leptodactylus Fitzinger, 1826 (Anura, Leptodactylidae), from the early Pliocene of the South American Pampas - Gomez, Raul Orencio (2013)
The Neotropical frog genus Leptodactylus is one of the most taxonomically diverse of all neobatrachian anurans. Despite the genus being highly diversified and widely distributed today, the fossil record is scanty and restricted to the Quaternary of the Neotropics. Here, we report and describe a new record of total group Leptodactylus from the Chapadmalalan (early Pliocene) of the South American Pampas. We evaluate both qualitative and quantitative characters and discuss the taxonomic value of body size in the context of living Leptodactylus. A number of features of the fossil elements suggests an affinity with the living species of the L. latrans species group and, particularly, with L. latrans. However, the lack of resolution of Leptodactylus interrelationships and, thus, the lack of osteological synapomorphies of the species groups and species within the genus conspire to force allocation of the fossils to crown Leptodactylus until they are studied in a rigorous phylogenetic context. In any case, the new material constitutes the oldest record of total group Leptodactylus and extends their stratigraphic range back to the early Pliocene.